Assessing the Influence of Voluntary Disclosure on Audit Quality in Public Shareholding Companies Listed on the Amman Stock Exchange (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study aims to examine the link between voluntary disclosure and audit quality in public shareholding companies (PSCs) on the Amman Stock Exchange (ASE). It also examines the effects of voluntary disclosure of financial analysis results and ratios, future information, and social responsibility on auditing quality through three sub-questions. The results indicate that there is a statistically significant effect of voluntary disclosure on audit quality in PSC in ASE. On the other hand, there is no statistically significant effect of voluntary disclosure of financial analysis results and ratios on audit quality. Conversely, the study reveals a statistically significant effect of voluntary disclosure of future information and social responsibility on audit quality. These results have important implications for enhancing transparency and accountability in PSC in the ASE. This study also contributes to clarifying the relationship between voluntary disclosure and audit quality, providing valuable insights for both companies and regulatory bodies
Keywords: Voluntary Disclosure; Audit Quality; Future Information; Social Responsibility